Effect of Fish Oil on Enteritis Damage and Intestinal Gene Expression Profiles in Vibrio parahaemolyticus Infected Mice - WANG Rundong, ZHOU Kui, DENG Yijia, ZHANG Yuhao, LI Xuepeng, LI Jianrong (Shipin Kexue, 2023)
Fish oil (FO) can modulate the gut ecosystem and improve intestinal health, but the specific role and mechanism of FO in preventing foodborne pathogen infection are still unclear. In this study, the effect of FO on enteritis damage and intestinal gene expression profiles in Vibrio parahaemolyticus (Vp) infected mice was investigated. The disease activity index (DAI) score, the colonic histopathological score (HIS), the expression of intestinal fibrosis biomarkers (type I and type III collagen), the contents of the cytokines interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNFα), the activities of the antioxidant enzymes catalase (AT), superoxide dismutase (SOD) and total antioxidant enzymes (TAE) and the colonic gene expression profiles in the mouse model of Vp infection were measured before and after FO intervention. The results showed that gavage with 4.0 mg/d FO significantly reduced DAI scores and HIS, and alleviated colonic pathological damage. FO could also significantly down-regulate the expression of intestinal fibrosis-related proteins (P < 0.05), maintain intestinal barrier functions, and inhibit cytokine-mediated excessive inflammation and oxidative stress. Thus, FO reduced body damage induced by Vp infection by altering the gene expression pattern in the colon, up-regulating the gene expression of peroxisome proliferator activated receptor (PPAR), enriching the PPAR signaling pathway, and inhibiting the nuclear factor-κB signaling pathway. Hence, dietary supplementation of FO can protect the body against foodborne pathogens.